Il calcio come gioco profondo della contemporaneità - Nesti, Romina (Studi sulla Formazione/Open Journal of Education, 2023)
The topic aims to reflect on the relationship and role that football has within contemporary society starting from Geertz’s concept of deep play and from the reflections on this sport by sociologists and anthropologists. Finally, brief reflections are then made on how a deep play can influence the educational processes.